مستقبل الطاقات المتجددة في الجزائر- قدرات عالية تفتقر لحسن الاستغلال - بن طجين محمد عبد الرحمان; عباده عبد الرؤوف (جامعة الوادي University Of Eloued, 2024)
يعتبر موضوع الطاقة بصفة عامة و الطاقات المتجددة بصفة خاصة من بين المواضيع التي استحوذت على اهتمام عالمي، خاصة خلال فترات الازمات الاقتصادية و السياسية، التي تنعكس على أسعار الطاقة بشكل او بآخر. من جهة أخرى تنادي العديد من المنظمات البيئية بتبني سياسات للتقليل من الغازات الدفيئة. تلك الأسباب و غيرها جعلت الحكومات في تسابق نحو استغلال مصادر الطاقات المتجددة. بذلت الجزائر بدورها العديد من الجهود في هذا الموضوع، من خلال وضع العديد من القوانين بالاضافة الى انشاء الكثير من الهيئات بالإضافة الى تسطير برامج لتحولها الطاقوي. وعليه ارتأينا ان يكون الهدف من خلال هذه الورقة ؛ البحث في مدى نجاح برنامج التحول الطاقوي للجزائر. الا أن ما خلصنا اليه من خلال دراستنا هو عدم بلوغ الحكومة إلى مرادها، بالرغم من القدرات الهائلة التي تستحوذ عليها الجزائر. و هو ما يعكسه حجم الإنتاج مقارنة بما هو مسطر في البرامج. The issue of energy, and in particular renewable energies, is among the topics of global concern, especially in periods of economic and political crises, which are reflected in energy prices. On the other hand, environmental organizations are calling for adopting policies to reduce greenhouse gases. Algeria has made many efforts towards energy transformation, by enacting many laws and establishing many bodies, in addition to developing programs for its energy transformation. Therefore, we decided that the goal of this paper would be to investigate the extent of the success of Algeria’s energy transition program. However, what we concluded through our study is that the government has not achieved its goals, despite the enormous capabilities that Algeria possesses. This is reflected in the volume of production compared to what is written in the programmes
The future of renewable energies in Algeria_ high capabilities lack good exploitation
Keywords: طاقة; طاقات متجددة; انبعاث ثاني اكيد الكربون; تحول طاقوي; Energy; Renewableénergies; Carbon dioxide emissions; energytransition